Organoleptic Quality of Egg Chips at Various Types and Levels of Fillers - Hikmah, Hikmah; Kartina, Kartina; Nahariah, Nahariah (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2023)
Egg chips are not yet common in society; therefore it is necessary to require attention for consumer assessments. Consumer ratings of egg chips indicate that consumers can accept egg chip products. The study aims to determine the effect of adding the types and levels of filler on the organoleptic quality of egg chips. Eighty-one eggs were used in the research. The studies were arranged based on a completely randomized design with a 3 x 3 factorial pattern with 3 replications. The first factor consisted of 3 types of fillers; there are tapioca powder, soybean protein isolate, and porang powder. The second factor was the level of filler (%) 3, 6, and 9 respectively. The parameters measured were egg chips' organoleptic quality (aroma, color, texture, and fondness). The results data indicated that the types and levels of fillers had a highly significant effect (P<0.01) on aroma egg chips. There was an interaction between types and levels of filler on the aroma. There was no significant difference (P>0.05) in color, texture, and fondness for egg chips. Adding the type and level of filler material could improve the organoleptic quality of egg chips. The addition of 9% of tapioca powder can increase the aroma of egg chips. Keywords: Egg powder, egg chips, organoleptic